Intradermal air pouch leukocytosis as an in vivo test for nanoparticles - Vandooren, Jennifer (Dove Medical Press, 2013)
The need for test systems for nanoparticle biocompatibility, toxicity, and inflammatory or adaptive immunological responses is paramount. Nanoparticles should be free of microbiological and chemical contaminants, and devoid of toxicity. Nevertheless, in the absence of contamination, these particles may still induce undesired immunological effects in vivo, such as enhanced autoimmunity, hypersensitivity reactions, and fibrosis. Here we show that artificial particles of specific sizes affect immune cell recruitment as tested in a dermal air pouch model in mice. In addition, we demonstrate that the composition of nanoparticles may influence immune cell recruitment in vivo. Aside from biophysical characterizations in terms of hydrodynamic diameter, zeta potential, concentration, and atomic concentration of metals, we show that – after first-line in vitro assays – characterization of cellular and molecular effects by dermal air pouch analysis is straightforward and should be included in the quality control of nanoparticles. We demonstrate this for innate immunological effects such as neutrophil recruitment and the production of immune-modulating matrix metalloproteases such as MMP-9; we propose the use of air pouch leukocytosis analysis as a future standard assay.